Investigation on the Mechanical and Morphological Properties of Regular and Irradiated Waste PET Modified Asphaltic Concrete Mixtures - Santhanasamy, Rickey (Universiti Teknologi PETRONAS, 2020)
Damages on road pavement such as fatigue failures are mainly due to the repetitive loading or weight contributed by increasing number of vehicles using road pavements as main mode of transportation. Meanwhile, Polyethylene Terephthalate (PET) is a non-biodegradable semi-crystalline thermoplastic polymer which is one of the major types of plastics waste. This large amount of PET waste generally, water bottles, are harmful to the environment causing hazards when disposed in landfills. There are existing studies on the use of PET as aggregates with mixed outcomes on the performance of asphaltic mixture. In concrete, the use of waste PET as secondary material showed a decreasing trend in compressive strength but exposing the waste PET to gamma radiation increases the degree of crystallinity of the waste PET which in turn makes the waste PET stiffer, stronger, and, tougher and therefore, recovers the lost strength. Hence, this project aims to evaluate the effects and characterization of utilizing regular and irradiated waste PET as an aggregate replacement on the mechanical properties of asphalt concrete mixtures.